The Effect of Medical Managers' Accountability To Managerial Performance: The Role Of Commitment As Mediating Variable - Suryo Pratolo; Tiyas Puji Utami (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Research Objective: This research aims to test the felt accountability of medical managers who have a hybrid role in improving managerial performance, through commitment as a mediating variable. Method/approach: This research is survey research using questionnaires distributed directly to respondents. The data obtained consisted of 460 medical manager respondents from Community Health Centers (Puskesmas) and Pratama Clinics. Sampling used purposive sampling technique. Data analysis was carried out using structural equation models. Results: The research results show that medical managers who have a sense of accountability or responsibility for their managerial work will be more motivated to improve managerial performance through their commitment. Practice implications: Its importance for complex organizations such as Healthcare. Specifically, this research offers insight into organizational support for hybrid identity constructs, such as a doctor taking on the role of medical manager. Originality/novelty: Research on felt accountability is still rarely carried out, especially in developing countries like Indonesia.